2012
DOI: 10.1017/s0967199412000020
|View full text |Cite
|
Sign up to set email alerts
|

Chilling curves for Piaractus mesopotamicus (Holmberg, 1887) embryos stored at −8°C

Abstract: The present study investigates the effect of different slow chilling curves on the storage of pacu (Piaractus mesopotamicus) embryos submitted to chilling at -8°C. Embryos at the blastopore closure stage were divided into two groups: G1 - embryos exposed to cryoprotectant solution containing methanol (10%) and sucrose (0.5 M), treated as follows: (T1) taken directly from room temperature to the refrigerator without being submitted to the curve; (T2) chilling curve of 0.5°C/min; and (T3) chilling curve of 1°C/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…When cells are submitted to low temperatures, there is a reduction in cellular and enzyme activities [16,27]. Thus, it was expected that after returning to room temperature, cellular activities would be restored and the embryonic period would be delayed for a certain time corresponding to the chilling period, similar to what has been observed in studies with other species [18,19]. However, the S parahybae embryos at the embryonic stage that usually presented the best results behaved differently.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…When cells are submitted to low temperatures, there is a reduction in cellular and enzyme activities [16,27]. Thus, it was expected that after returning to room temperature, cellular activities would be restored and the embryonic period would be delayed for a certain time corresponding to the chilling period, similar to what has been observed in studies with other species [18,19]. However, the S parahybae embryos at the embryonic stage that usually presented the best results behaved differently.…”
Section: Discussionmentioning
confidence: 67%
“…3). Embryos at the free-tail embryonic stage (19 hpf, mean water temperature: 26.25 AE 0.40 C) were counted (100 per replication) and placed in Falcon tubes (50 mL), where they received 10 mL of cryoprotectant solution: M10 þ S (10% methanol [Merck] and 0.5-M sucrose), and then subjected to a chilling curve as described by Lopes et al [19]. They were then taken to the refrigerator, kept for 6 and 12 hours at subzero temperatures (À6.44 AE 1.39 C), and then transferred to conical hatcheries (1.5 L), remaining there until the moment of hatching.…”
Section: Test Iii: Chilling Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to test new cryoprotectants with the same characteristics. Methanol has properties that are common among short-chain alcohols, such as the ability to lower the phase transition temperature of the lipid membrane; and this mechanism of protection reported positive results for the cryopreservation of fish embryos (LOPES et al, 2012(LOPES et al, , 2015. Solutions of PG promoted small and amorphous ice formation due to their high viscosity at temperatures below zero.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high sensitivity to cold reported in the literature for temperate climate fish species, such as Sciaenops ocellatus and Tinca tinca (Gwo et al, 1995;ElBattawy, Linhart, 2009), and neotropical species, such as Piaractus mesopotamicus Lopes et al, 2013), cooling protocols use temperatures below or close to 0ºC in their attempt to prolong embryonic development by long periods (Ninhaus-Silveira et al, 2006;Fornari et al, 2012). Thus, in this study, it was found that the use of a higher temperature (5ºC) allowed an increase in tropical fish embryonic survival and prolonged embryonic development time sufficiently to achieve a 12-h cooling technique, although morphological damage could not be controlled.…”
Section: Discussionmentioning
confidence: 99%